2000
DOI: 10.1002/1096-911x(20001201)35:6<659::aid-mpo38>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of buthionine sulfoximine and melphalan against neuroblastoma cell lines derived after disease progression

Abstract: Fixed ratio analysis demonstrated BSO/L-PAM synergy (combination index >1) for all cell lines tested. In L-PAM-resistant cell lines, the minimal cytotoxicity observed for BSO combined with nonmyeloablative concentrations of L-PAM was markedly enhanced (>4 logs total cell kill) when BSO was combined with myeloablative concentrations of L-PAM. In alkylator-resistant NB, the optimal use of BSO may require dose escalation of L-PAM to levels requiring AHSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Potentially, Fe-SP-mediated ROS generation may exert synergistic effects when combined with other agents, thought to modulate the antioxidant functions of cancer cells, for example 2-methoxyestradiol (SOD inhibitor), tetrathiomolybdate or ATN-224 (copper-depletion agents to target Cu/Zn SOD) and buthionine-sulfoximine (inhibitor of glutathione/GSH synthesis). Buthionine-sulfoximine has been intensively investigated and in NB cells potentiated the chemotherapeutic effect of melphalan [36]. In line with these findings, it can also be postulated that the use of different agents leading to GSH depletion (such as isothiocyanate and aziridine analogues) may express therapeutic potential to sensitize cells when combined with ROS-generating chemotherapy through drugs such as Fe-SP.…”
Section: Discussionmentioning
confidence: 86%
“…Potentially, Fe-SP-mediated ROS generation may exert synergistic effects when combined with other agents, thought to modulate the antioxidant functions of cancer cells, for example 2-methoxyestradiol (SOD inhibitor), tetrathiomolybdate or ATN-224 (copper-depletion agents to target Cu/Zn SOD) and buthionine-sulfoximine (inhibitor of glutathione/GSH synthesis). Buthionine-sulfoximine has been intensively investigated and in NB cells potentiated the chemotherapeutic effect of melphalan [36]. In line with these findings, it can also be postulated that the use of different agents leading to GSH depletion (such as isothiocyanate and aziridine analogues) may express therapeutic potential to sensitize cells when combined with ROS-generating chemotherapy through drugs such as Fe-SP.…”
Section: Discussionmentioning
confidence: 86%
“…BSO, as a single agent, is highly cytotoxic for neuroblastoma cell lines in vitro due to increased generation of reactive oxygen species (ROS), but BSO single agent activity is minimal at physiological oxygen concentrations . Combining BSO with clinically achievable (non‐myeloablative) concentrations of L‐PAM was highly synergistic for neuroblastoma cell lines, including those lacking functional p53 . Preclinical toxicology studies in animals showed no major toxicity at doses of BSO used in this trial …”
Section: Introductionmentioning
confidence: 75%
“…[16] Combining BSO with clinically achievable (non-myeloablative) concentrations of L-PAM was highly synergistic for neuroblastoma cell lines, including those lacking functional p53. [17] Preclinical toxicology studies in animals showed no major toxicity at doses of BSO used in this trial. [18,19] Clinically, BSO has been given to adults in combination with L-PAM, with the reported systemic toxicities being largely reversible myelosuppression and with responses observed in patients with melanoma, ovarian cancer, breast cancer, and small cell carcinoma of the lung.…”
Section: Introductionmentioning
confidence: 76%
“…The latter observation suggests that methods for detecting p53 functionality in clinical specimens will be required to complement detection of mutations. Finally, demonstrating that high-level drug-resistance is associated with p53-LOF suggests that p53-independent therapies (e.g., ceramide modulators [21], BSO/L-PAM [25]) or immunotherapy [26] should be employed in recurrent neuroblastomas.…”
Section: Discussionmentioning
confidence: 99%